Fine-Grained Energy Profiling for Power-Aware Application Design - Kansal, Aman; Zhao, Feng (First Workshop on Hot Topics in Measurement and Modeling of Computer Systems (HotMetrics08) at ACM Sigmetrics. (Archived in SIGMETRICS Perform. Eval. Rev.), 2008)
Signiﬁcant opportunities for power optimization exist at application design stage and are not yet fully exploited by system and application designers. We describe the challenges developers face in optimizing software for energy efﬁciency by exploiting application level knowledge. To address these challenges, we propose the development of automated tools that proﬁle the energy usage of various resource components used by an application and guide the design choices accordingly. We use a preliminary version of a tool we have developed to demonstrate how automated energy proﬁling helps a developer choose between alternative designs in the energy performance trade-off space.